The relationship between weight and smoking in a national sample of adolescents: Role of gender. (December 2015) - Lange, Krista; Thamotharan, Sneha; Racine, Madeline; Hirko, Caroline; Fields, Sherecce
This study sought to investigate the role of weight status and body mass index percentile in risky smoking behaviors in male and female adolescents. Analyses of the data obtained in the 2011 Youth Risk Behavior Surveillance System were conducted. The national sample size included 15, 425 adolescents. Questions addressing weight status and smoking behaviors were used in analyses. Significant effects of perceived weight status, weight change status, and body mass index percentile on smoking behaviors were found for both genders. The current findings indicate the importance of accounting for both gender and weight status when developing prevention and cessation programs targeting smoking behaviors.